Concrete-filled double-skin aluminum circular hollow section stub columns. (December 2018) - Zhou, Feng; Young, Ben
Abstract: This paper presents experimental and numerical investigations and design of concrete-filled double-skin aluminum stub columns with circular hollow sections (CHS) as both outer and inner skins. A series of tests was carried out to investigate the effects of the geometric dimension of the aluminum CHS and concrete strength on the behaviour and strength of the composite columns. The CHS tubes were fabricated by extrusion using 6061-T6 heat-treated aluminum alloy having nominal 0.2% proof stress of 240 MPa. The structural performance of the composite columns was investigated using different nominal concrete cylinder strengths of 40, 70 and 100 MPa. A non-linear finite element model is developed and verified against the experimental results. The test results and the composite column strengths predicted from the finite element analysis (FEA) were compared with the design strengths to evaluate the reliability of the design rules in the current American specifications for aluminum and concrete structures. Furthermore, design equations were proposed to consider the benefits of the composite columns due to the composite action between the aluminum tubes and concrete. The proposed design equations accurately predicted the ultimate strengths of the concrete-filled double-skin aluminum CHS stub columns. Highlights: Concrete-filled double-skin aluminum circular hollow section stub columns are tested. A finite element model is developed and verified against the experimental results. The current design rules for aluminum and concrete structures are evaluated. The benefits of the composite action is considered in the proposed design equations.